INTERNUCLEAR OPHTHALMOPLEGIA IN MULTIPLE SCLEROSIS PATIENT - Tirkal, Fahrian; Mansyur, Yunita; Umar, Batari Todja; Baan, Junus; Goysal, Yudy (Majalah Oftalmologi Indonesia, 2024)
Introduction: Internuclear ophthalmoplegia (INO) characterized by impaired adduction of the affected eye caused by a lesion in the medial longitudinal fasciculus (MLF). The common cause of INO is demyelinating disease including multiple sclerosis. INO arguably the most discrete localizing sign in medicine, has considerable value in predicting multiple sclerosis. Due to its high spatial resolution, MRI has allowed us to depict in vivo the anatomic organization of the human oculomotor nerve complex, the MLF, and related structures in the brainstem. Case Report: A 48-year-old female presented with blurred vision of both eyes for 2 weeks, but then slowly resolved. Best corrected visual acuity presentation on both eyes were 20/20 with normal intraocular pressure (IOP). Adduction deficit observed on the left eye with no nystagmus. Convergence are not impaired in both eyes. Anterior segments was normal except minimal lens cloudiness in both eyes. Funduscopic examination result also within normal limit. Patient had undergone Computerised Tomography (CT-Scan) and the result was normal, no ischemic area or Space occupied lesion (SOL) or intracranial bleeding were found. Brain MRI showed bilateral optic perineuritis and multiple lesion in bilateral frontoparietalis and in the left side of the pons suggested multiple sclerosis. Discussion: Impairment of adduction movement on the patient’s left eye caused by demyelinating plaque related multiple sclerosis on the left side of the pons as shown MRI imaging. Management in this patient is based on the underlying condition. Conclusion: Internuclear ophthalmoplegia in this cases maybe caused by lesion in the medial longitudinal fasciculus could be related with multiple sclerosis.